A multilevel hybrid chaotic cryptosystem and authentication algorithm for digital images - Verma, Vinay (My University, 2015)
In this thesis, a multilevel hybrid chaotic cryptographic system for digital images is proposed. It is basically combination of public and private keys or hybrid technique to encrypt the image. Plain and secret images are encrypted using RSA algorithm using p and q rounds of execution respectively. Cipher images are generated using XOR operations on encrypted plain and secret images. To show the effectiveness of the proposed system, NPCR and UACI metric have been calculated for five text images for five rounds. In each round, public key encryption is applied in the form of RSA. Due to some iteration applied on the chaotic system to obtain the cipher-image the security level will increase. In another work, Hashing based image authentication is proposed based on the multiple transformations i.e. Discrete Wavelet Transform (DWT) with the log-polar transform. DWT jointly deal with all the three combination of color in an image and also it uses very less computation time with respect to other transformations. The main features of the proposed method are based on (i) the secondary image is obtained by log polar transform and (ii) the addition of images that are formed by log polar transform with the output of the DWT applied on the image after pre-processing. The final hash image is generated by applying the Arnold transformation on the result image according to the correlation of these magnitude coefficients and is scrambled by a secret key to enhance the system security. Various results are obtained by conducting some experiments in order to analyze and identify the most appropriate parameter values of the method that has been proposed and also results show that quality of image is not much distracted in proposed method. This scheme also shows the better sensitivity when changing the little part of image.
M.Tech-Computer Science Applications-Thesis
Keywords: Chaotic; NPCR; UACI; DWT; Hashing; PSNR; CSE; computer science